Human Resource Planning and Development in Islamic Educational Institutions - Lutfi Firdausi (Journal of Educational Research and Practice, 2025)
This research is motivated by issues in human resource (HR) management in Islamic educational institutions, which still face challenges in aspects of planning, competency development, and the integration of Islamic values into managerial practices. Many Islamic educational institutions do not yet have a directed, sustainable HR management system that aligns with the demands of the modern era, resulting in low professionalism among educators and overall institutional effectiveness. This study uses a library research method by analyzing literature related to modern HR management theory, particularly Gary Dessler's theories, and linking them to management principles from an Islamic perspective. The findings indicate that effective HR planning, sustainable development strategies, and the integration of Islamic spiritual values are key factors in improving the performance of Islamic educational institutions. In addition, the application of the strategic human resource management concept combined with the values of trustworthiness, justice, and excellence can create a professional, ethical, and quality-oriented management system. The implications of this research emphasize that Islamic educational institutions need to develop a human resource management model based on Islamic values that is adaptive to changes in the times, in order to produce educators who are not only academically competent but also possess high moral and spiritual integrity.